Customer Satisfaction in The Hospitallity Sector: a Narrative Literature Review - Widiyanti, Wiwik; Tukiran, Martinus; Rani; Syahrir (IJOSMAS, 2024)
The research aims to create a narrative literature review with the title Customer satisfaction in the hospitality sector, in particular in the area of hotels, restaurants, and online travel agencies. The research uses three journals as data sources, namely: (1) a journal on customer satisfaction with hotels based on analysis of reviews generated by consumers; (2) a journal on factors that influence customer satisfaction in the restaurant business based on empirical studies from Bangladesh; and (3) a journal on the factors that affect customer content from online travel agencies in India. The study has two research questions, namely: (1) What are the customer satisfaction factors in hospitality? (2) Are there differences in customer satisfaction in the areas of hotels, restaurants, and online travel agencies? The results of this study show that: (1) customer satisfaction factors in hospitality include intrinsic and extrinsic factors that have a different impact depending on the type and level of product or service offered; and (2) there are differences in customer satisfaction in the areas of hotels, restaurants, and online travel agencies caused by different characteristics, expectations, and preferences of customers in each area. This research provides some recommendations to hospitality entrepreneurs on how to identify factors that affect customer satisfaction and adapt them to market conditions and segmentation.